ADAPTASI BUDAYA MAHASISWA INDONESIA SELAMA MENEMPUH PENDIDIKAN DI TURKI - Aisyah Nadhilah Arsyi Malik; Turnomo Rahardjo; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
One situation where cultural adaptation happens frequently in society is when a person moves to a location that is considerably different from his or her usual environment. Students who relocate to foreign nations also experience this; they struggle to fit in with their new surroundings. Many elements that make it challenging for pupils to adapt are typically brought on by the new environment, culture, conventions, and rules. The question of how these Indonesian students can adjust to a new environment and culture then arises for students who are immigrating to other nations. This study uses qualitative research techniques in conjunction with interpretive paradigms and phenomenological approaches to learn more about the adjustment process of Indonesian students while they are studying in Turkey. In-depth interviews are the method of data collecting used. The U-curve theory, cultural identity theory, culture shock theory, and cultural adaptation theory were the theories employed in this study. The findings of this study show that there are four stages in the process by which Indonesian students adjust to their new cultural environment while studying in Turkey. The first stage involves acclimating to the new environment, followed by the second stage, which is known as culture shock. Students experience anxiety and fear at this stage. due to different religious beliefs, language, cuisine, lifestyle, and culture, as well as homesickness. The life of Indonesian students in Turkey once they have adjusted to the country's surroundings and culture follows the culture shock phase. Identity formation is the last stage that Indonesian students go through. Because of the interactions amongst Indonesian students, identity is formed